Supramolecular scaffolds on glass slides as sugar based rewritable sensors for bacteria. Issue 29 (12th March 2015) - Gade, Madhuri; Paul, Ajay; Alex, Catherine; Choudhury, Devika; Thulasiram, Hirekodathakallu V.; Kikkeri, Raghavendra
Abstract : We describe here the sugar functionalized β-cyclodextrin–ferrocene glass slides as fully reversible bacterial biosensors under the influence of external adamantane carboxylic acid. Abstract : We describe here the sugar functionalized β-cyclodextrin–ferrocene glass slides as fully reversible bacterial biosensors under the influence of external adamantane carboxylic acid. The prototyped -mannose – E. coli ORN 178 andl -fucose – P. aeruginosa interactions serve as a model to illustrate the new approach.